Cover Image. Issue 1 (1st November 2022) - Florczyk, Stephanie J.; Hotaling, Nathan A.; Simon, Mylene; Chalfoun, Joe; Horenberg, Allison L.; Schaub, Nicholas J.; Wang, Dongbo; Szczypiński, Piotr M.; DeFelice, Veronica L.; Bajcsy, Peter; Simon, Carl G.
Abstract : The cover image is based on the Research Article Measuring dimensionality of cellscaffold contacts of primary human bone marrow stromal cells culturedon electrospun fiber scaffolds by Stephanie J. Florczyk et al., https://doi.org/10.1002/jbm.a.37449 .